The effect of destination attractiveness on destination attachment and its impact on tourist sustainable behavior - Sri Astuti Pratminingsih; Ahmad Johan; Imanirrahma Salsabil (Jurnal Siasat Bisnis, 2022)
Purpose – In gaining competitive advantage in the tourism context, Bandung City needs a good marketing strategy. This study aims to determine the influence of destination attractiveness on destination attachment and its impact on tourist sustainable behavior in Bandung, West Java. Design/methodology/approach – This study used a descriptive verification approach. The number of samples is 151 tourists who were randomly selected using incidental techniques. The data analysis is carried out using SEM with Amos 22 software. The data were collected through questionnaire, notes and publication, and literature study. Findings – The results of this study indicate that the attraction given by a destination directly influences tourists to make return visits. Destination attractiveness has an influence on destination attachment. This study also found that the mediating effect of the tourist destination attachment on the relationship between destination attractiveness and sustainable behavior is very small. Research limitations/implications – Future research is suggested to consider other variables that are able to mediate the influence of tourist attraction on return visits or sustainable behavior. Practical implications – As destination attractiveness positively affects sustainable behavior of tourist, this study provides insight for the government of Bandung city to make a good marketing strategy in order to create a competitive advantage in their destination. Originality/value – This study answers to the suggestion from previous studies to identify and examine the mediators relevant to the attitude-behavior relationship in the context of tourism research.